2022
DOI: 10.1021/acscatal.1c05590
|View full text |Cite
|
Sign up to set email alerts
|

Antisintering Pd1 Catalyst for Propane Direct Dehydrogenation with In Situ Active Sites Regeneration Ability

Abstract: Atomically dispersed Pd (Pd 1 ) catalysts supported on annealed nanodiamond were prepared through a deposition−precipitation method toward propane direct dehydrogenation (PDDH). The Pd 1 catalyst is superior to Pd cluster/particle catalysts in activity and stability. Combining experimental characterizations and DFT calculations revealed that atomically dispersed Pd species have strong interactions with the hybrid nanodiamond/graphene support, leading to better resistance to coke formation. More importantly, Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…1,2 Propylene is primarily produced by direct dehydrogenation (DH), which is endothermic, equilibrium limited, and requires significant energy input. 3 Currently, the propane dehydrogenation (PDH) is considered as an economically and environmentally friendly route to produce about 10% of the global propylene. 4 The direct DH is endothermic in nature; to achieve acceptable conversion and high yield of target olefins, substantial energy input and high temperature are required, and the overall energy efficiency is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Propylene is primarily produced by direct dehydrogenation (DH), which is endothermic, equilibrium limited, and requires significant energy input. 3 Currently, the propane dehydrogenation (PDH) is considered as an economically and environmentally friendly route to produce about 10% of the global propylene. 4 The direct DH is endothermic in nature; to achieve acceptable conversion and high yield of target olefins, substantial energy input and high temperature are required, and the overall energy efficiency is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Propylene is regarded as one of the most important building blocks for producing polypropylene, propylene oxide, acrylonitrile, and related chemicals. , Propylene is primarily produced by direct dehydrogenation (DH), which is endothermic, equilibrium limited, and requires significant energy input . Currently, the propane dehydrogenation (PDH) is considered as an economically and environmentally friendly route to produce about 10% of the global propylene .…”
Section: Introductionmentioning
confidence: 99%
“…82-84, 95, 96 Moreover, aggregation can be an additional factor, even though, we did not observe Pd agglomerates on AFM images, one cannot fully exclude agglomeration to some extent It was also shown that Pd 1 is stable on nanodiamonds under propane dehydrogenation conditions. 63 Catalytic performance of the Cu 1 Pd 3 , Cu 2 Pd 2 and Cu 3 Pd 1 mixed tetramers on TiO 2 support From the UNCD and ZrO 2 -supported mixed four-atom clusters, only the zirconia-supported Cu 1 Pd 3 , Cu 2 Pd 2 and Cu 3 Pd 1 tetramers produced cyclohexadiene, moreover, exhibiting a strongly composition-dependent selectivity for C6 products cyclohexadiene and benzene. In order to further explore the effect of support, a reducible oxide support TiO 2 was chosen to complement the UNCD and the non-reducible zirconia supports.…”
Section: Faraday Discussion Accepted Manuscriptmentioning
confidence: 99%
“…4 The subnanometric Pt clusters can achieve maximum atomic utilization, reduce the active sites for side reactions and enhance propylene desorption. [5][6][7] Nevertheless, Pt clusters are prone to agglomeration or sintering at the high temperature of PDH (4550 1C), owing to the relative high surface free energies. Therefore, maintaining the stability of Pt clusters remains a challenge, which can be overcome by finding appropriate anchoring supports.…”
Section: Introductionmentioning
confidence: 99%
“…In the works of Liu's group, they synthesized core-shell nanodiamond@graphene hybrid supports to anchor Pt nanoparticles or clusters for alkane dehydrogenation. 5,8,[16][17][18] The results showed that Pt clusters would bind strongly with the C atoms around vacancies, thus enhancing the interaction between Pt clusters and supports. Meanwhile, our previous theoretical work 19 systemically designed carbon materials with various vacancies to anchor the Pt single atom for PDH.…”
Section: Introductionmentioning
confidence: 99%